Using a mixed‐methods approach to adapt an HIV stigma reduction to address intersectional stigma faced by men who have sex with men in Ghana. (12th July 2022) - Nyblade, Laura; Stockton, Melissa A.; Saalim, Khalida; Rabiu Abu‐Ba'are, Gamji; Clay, Sue; Chonta, Mutale; Dada, Debbie; Mankattah, Emmanuel; Vormawor, Richard; Appiah, Patrick; Boakye, Francis; Akrong, Ransford; et al.
Abstract: Introduction: In Ghana, men who have sex with men (MSM) are estimated to be 11 times more likely to be living with HIV than the general population. Stigmas at the intersection of HIV, same‐sex and gender non‐conformity are potential key drivers behind this outsized HIV disease burden. Healthcare workers (HCWs) are essential to HIV prevention, care and treatment and can also be sources of stigma for people living with HIV and MSM. This article describes the process and results of adapting an evidence‐based HIV stigma‐reduction HCW training curriculum to address HIV, same‐sex and gender non‐conformity stigma among HCWs in the Greater Accra and Ashanti regions, Ghana. Methods: Six steps were implemented from March 2020 to September 2021: formative research (in‐depth interviews with stigma‐reduction trainers [ n = 8] and MSM living with HIV [ n = 10], and focus group discussions with HCWs [ n = 8] and MSM [ n = 8]); rapid data analysis to inform a first‐draft adapted curriculum; a stakeholder adaptation workshop; triangulation of adaptation with HCW baseline survey data ( N = 200) and deeper analysis of formative data; iterative discussions with partner organizations for further refinement; external expert review; and final adaptation with the teams of HCWs and MSM being trained to deliver the curriculum. Results: Key themes emerging under four immediately actionable drivers of health facility intersectional stigma (awareness, fear, attitudes and facility environment) informed the adaptation of the HIV training curriculum. Based on the findings, existing curriculum exercises were placed in one of four categories: (1) Expand—existing exercises that needed modifications to incorporate deeper MSM and gender non‐conformity stigma content; (2) Generate—new exercises to fill gaps; (3) Maintain—exercises to keep with no modifications; and (4) Eliminate—exercises that could be dropped given training time constraints. New exercises were developed to address gender norms, the belief that being MSM is a mental illness and stigmatizing attitudes towards MSM. Conclusions: Getting to the "heart of stigma" requires understanding and responding to both HIV and other intersecting stigma targeting sexual and gender diversity. Findings from this study can inform health facility stigma reduction programming not only for MSM, but also for other populations affected by HIV‐related and intersectional stigma in Ghana and beyond.